LncRNAs Regulate Vasculogenic Mimicry in Human Cancers - Eloísa Ibarra-Sierra; Mercedes Bermúdez; Carlos Esteban Villegas-Mercado; Macrina B. Silva-Cázares; César López-Camarillo (Cells)
Vasculogenic mimicry (VM) has recently been discovered as an alternative mechanism for nourishing cancer cells in vivo. During VM, tumor cells align and organize themselves into three-dimensional (3D) channel-like structures to transport nutrients and oxygen to the internal layers of tumors. This mechanism mainly occurs in aggressive solid tumors and has been associated with poor prognosis in oncologic patients. Long non-coding RNAs (lncRNAs) are essential regulators of protein-encoding genes involved in cancer development and progression. These single-stranded RNA molecules regulate critical cellular functions in cancer cells including cell proliferation, apoptosis, angiogenesis, VM, therapy response, migration, invasion, and metastasis. Recently, high-throughput RNA-sequencing technologies have identified thousands of lncRNAs, but only a small percentage of them have been functionally characterized in human cancers. The vast amount of data about its genomic expression in tumors can allow us to dissect their functions in cancer biology and make them suitable biomarkers for cancer diagnosis and prognosis. In this study, we reviewed the current knowledge about the role of lncRNAs in regulating VM in cancer. We also examined the molecular mechanisms of lncRNAs and highlight several commonalities in the cellular functions associated with VM between diverse cancer types. Future directions for research focused on deciphering their function in VM are delineated. Finally, the potential of selected lncRNAs as novel therapeutic targets in RNA-based molecular interventions is also discussed.